2010
DOI: 10.1007/s11999-010-1379-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly Crosslinked Polyethylene Reduces Wear in Total Hip Arthroplasty at 5 Years

Abstract: Highly crosslinked polyethylene undergoes substantially less wear than conventional polyethylene at medium term. The effect of hip arthroplasty longevity will need to be assessed with longer-term studies, but this may lead to a decreased need for revision as a result of less wear and osteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 27 publications
3
52
2
1
Order By: Relevance
“…This is likely attributable to the superior accuracy and precision of the RSA method. The 2-D wear rate observed in our study was more than three times less than that reported by Mutimer et al [24]. Possible explanations for the larger wear rate reported is that the patient cohorts may have been different, and the wear was calculated after 6 months which may have been insufficient to account for all of the creep and bedding-in.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…This is likely attributable to the superior accuracy and precision of the RSA method. The 2-D wear rate observed in our study was more than three times less than that reported by Mutimer et al [24]. Possible explanations for the larger wear rate reported is that the patient cohorts may have been different, and the wear was calculated after 6 months which may have been insufficient to account for all of the creep and bedding-in.…”
Section: Discussioncontrasting
confidence: 73%
“…Five recent studies [1,11,12,20,24] measured femoral head penetration of the Marathon TM polyethylene liner, with at least 5 years of followup using computer-based analyses of plain radiographs ( Table 2). The 2-D wear rate measured in our study, 0.014 mm/year, was at the lower end of these varying reports and with a smaller range of results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly crosslinked ultrahigh-molecular-weight polyethylene (XLPE) has demonstrated superior wear performance compared with conventional polyethylene (PE) in THA with followup studies beyond 10 years showing few or no patients with osteolysis [5,6,10,21,24,26,32]. XLPE was more recently introduced into TKA after in vitro knee simulator findings of lower wear rates compared with those found with conventional PE [12,22,33,34].…”
Section: Introductionmentioning
confidence: 99%